2018
DOI: 10.1038/s41598-018-34355-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical controls on the propagation rate of fracture in calcite

Abstract: Calcite (CaCO3) is one of the most abundant minerals in the Earth’s crust, and it is susceptible to subcritical chemically-driven fracturing. Understanding chemical processes at individual fracture tips, and how they control the development of fractures and fracture networks in the subsurface, is critical for carbon and nuclear waste storage, resource extraction, and predicting earthquakes. Chemical processes controlling subcritical fracture in calcite are poorly understood. We demonstrate a novel approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…Cleaving experiments of calcite through the (101̅4) plane in different pH solutions were conducted, and change in atomic corrugations on the surface was observed. , It was reported that the dissolution rate of calcites is dominated by etch pits . Ilgen et al conducted an experiment on crack initiation and crack propagation using a premade indented tip along the (101̅0) plane and reported that the dissolution rate of calcite in various solutions increased when the solutions’ pH decreased. The crack propagation rate decreased gradually but showed weak dependence on pH and varied with different solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleaving experiments of calcite through the (101̅4) plane in different pH solutions were conducted, and change in atomic corrugations on the surface was observed. , It was reported that the dissolution rate of calcites is dominated by etch pits . Ilgen et al conducted an experiment on crack initiation and crack propagation using a premade indented tip along the (101̅0) plane and reported that the dissolution rate of calcite in various solutions increased when the solutions’ pH decreased. The crack propagation rate decreased gradually but showed weak dependence on pH and varied with different solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Some dissolution research studies were conducted on the {101̅4} plane cleaved , and the undefined plane of calcite crystals in an aqueous environment. The dissolution rate and the cleaved surface were examined by atomic force microscopy . Lardge and Wang suggested that ionic bonds form between the Ca 2+ and carbonate ions across the (101̅4) plane and that these bonds can be cleaved through this crystal plane by applying external stress.…”
Section: Resultsmentioning
confidence: 99%
“…The first phase of hydraulic fracturing (Figure ) is comprised of injecting a highly acidic “spearhead” fluid (7.5–15% HCl, pH < 0) intended to clean out the wellbore and dissolve reactive minerals (e.g., carbonates) in the near wellbore region to create pore openings that aid in fracture propagation. ,, High flow rates with associated small fracture apertures result in Pe ≫ 1 while the low-pH oxic environment results in extraordinarily high Da for reactive minerals. Acid from the initial spearhead is consumed and diluted over the steps of the fracturing operation, reducing its efficacy away from the wellbore, thereby resulting in a decrease in Da .…”
Section: The Hydraulic Fracturing Processmentioning
confidence: 99%
“…Other studies on calcite demonstrate inconsistent results as different concentrations of NaCl and H 2 SO 4 lead to weakening or strengthening compared to DI H 2 O (Bergsaker et al, 2016;Jouniaux et al, 2006;Liteanu & Spiers, 2009;Liteanu et al, 2013;Risnes et al, 2005;Rostom et al, 2012;Royne et al, 2011). Ilgen et al, 2018 observed that in nanoindented pre-fractured calcite single crystals the ability of anions to form surface complexes with calcium affected residual crack growth more compared to changes in the zeta-potential, pH, or calcite dissolution rate. They hypothesized that anions in the fluid form chemical complexes with calcium at the crack tip, limiting the availability of surface sites, and therefore limiting hydrolysis of Ca−CO 3 bonds (Ilgen et al, 2018).…”
mentioning
confidence: 94%
“…Ilgen et al., 2018 observed that in nanoindented pre‐fractured calcite single crystals the ability of anions to form surface complexes with calcium affected residual crack growth more compared to changes in the zeta‐potential, pH, or calcite dissolution rate. They hypothesized that anions in the fluid form chemical complexes with calcium at the crack tip, limiting the availability of surface sites, and therefore limiting hydrolysis of Ca−CO 3 bonds (Ilgen et al., 2018). The presence of anions which strongly complex with calcium increased effective fracture toughness.…”
Section: Introductionmentioning
confidence: 99%